Improving Student's Reading Comprehension Ability Using Jigsaw 1 Technique - Katemba, Caroline Victorine; Samuel, Samuel (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2017)
This research is entitled “Effectiveness of Utilizing Jigsaw 1 towards Improving Students’ Reading Comprehension Ability. The experimental design was used in this study. The participants of this study were two classes of grade 8 of Â junior high school in Parongpong Bandung, Indonesia; each class consisted of 32 participants in grade 8A as the experimental group and 33 participants in grade 8B as the control group. The experimental group was taught using Jigsaw 1 Technique and the control group was taught using conventional technique.Â This study intended to seek an answer on the question; Is there any significant difference on the effect of reading comprehension between those students who are using jigsaw-1 and those who are taught through the conventional method. This research was divided into three steps: giving a pre-test, treatment (Jigsaw 1 Technique) and the last giving post-test. Data analysis shows that there is a significant difference in the reading comprehension ability between those who were taught using Jigsaw 1 technique and those who were taught using the conventional techniques. Keywords: Jigsaw 1, Reading Comprehension